Dome-type carcinoma of the rectum mimicking a submucosal tumor: a case report and literature review - Byeong-Joo Noh; Sun Jin Park; Jae-Young Jang; Youn Wha Kim (Journal of Minimally Invasive Surgery)
Dome-type carcinoma (DC) has been recognized as a rare variant of adenocarcinoma, which arises in gut-associated lymphoid tissue. It has a specific morphologic feature of a dome-like protrusion associated with lymphoid tissue. We report a case of a DC of the rectum in an asymptomatic 58-year-old male. A 2-cm sized, well-demarcated, round mass masquerading as a submucosal tumor (SMT) was identified in the rectum and was resected by endoscopic submucosal dissection. The tumor was revealed as an adenocarcinoma with submucosal invasion of 3,700 μm, which consisted of dilated cystic glands and the lymphoid stroma with reactive germinal centers. On immunohistochemistry, the tumor cells revealed retained expression for mismatch repair proteins. Laparoscopic surgical resection was subsequently performed. DC is considered a distinctive subtype of colorectal adenocarcinoma with characteristic morphology and lowgrade malignant potential. Careful detection of the overlying mucosal lesion is crucial to differentially diagnose DC from SMT.